The Existence of Pyong Pyong Band in Semarang (Universitas Negeri Semarang, 2023)
Pyong Pyong Band is a pop punk band from Semarang formed on December 8, 1999. The purpose of this research was to describe and discuss the existence and the efforts of Pyong Pyong band to maintain its existence. This study used a phenomenological approach and qualitative methods. Data collection techniques were carried out through the stages of observation, interviews and documentation. Based on the results of the research and discussion, it was concluded that Pyong Pyong Band still exists today. This is evidenced by the increasing recognition by the public of the works of Pyong Pyong Band, including the number of Instagram followers which reached 3,806. Furthermore, to maintain its existence, Pyong Pyong Band makes efforts through activities by continuing to work in music, collaborating, and utilizing various social media in establishing communication with their fans as well as a medium to popularize his works.